Osteoprotegerin and RANKL serum concentrations in neonates of mothers with early-onset pre-eclampsia: comparison with neonates of normotensive mothers. (August 2019) - Oikonomou, Nikoleta; Papadopoulou, Chrysanthi; Fouzas, Sotirios; Kritikou, Dimitra; Chrysis, Dionisios; Sinopidis, Xenophon; Dimitriou, Gabriel; Karatza, Ageliki A.
Abstract: Background: Pre-eclampsia is a known risk factor for long-term cardiovascular complications. Osteoprotegerin (OPG) and the receptor activator of nuclear factor κB ligand (RANKL) have been implicated in the pathogenesis of cardiovascular disease. The OPG-RANKL axis function is also altered in pregnant women with pre-eclampsia, but there is lack of data regarding OPG and RANKL concentrations in their neonates. Aims: To examine the effects of early-onset pre-eclampsia on OPG and RANKL serum concentrations at birth, taking into account the influence of various perinatal factors. Study design: OPG and RANKL serum concentrations were measured in 28 premature newborns of mothers with early onset pre-eclampsia, and in 28 preterm and 28 full-term neonates of normotensive mothers (control groups). Results: Neonates of pre-eclamptic mothers had higher OPG and lower RANKL levels compared to both control groups (Kruskal-Wallis P < 0.0001 and P = 0.014, respectively). Regression analysis showed that pre-eclampsia (P < 0.0001), birth weight z-score (P = 0.048) and antenatal steroid administration (P = 0.034) were significant determinants of OPG levels. Multivariable regression analysis also showed that pre-eclampsia was an independent predictor of increased diastolic and mean blood pressure in these neonates. Conclusions: Early-onset pre-eclampsia affects OPG concentrations at birth and is an independent predictor of increased blood pressure in the offspring. Our findings suggest that altered OPG-RANKL axis function may be one of the mechanisms of cardiovascular 'programming' in fetuses exposed to pre-eclampsia. Highlights: OPGRANKL have been implicated in the pathogenesis of cardiovascular disease Serum OPG and OPG/RANKL are higher in newborns exposed to early-onset pre-eclampsia Pre-eclampsia is an independent predictor of high blood pressure in the offspring OPG may be involved in the cardiovascular 'programming' of pre-eclamptic fetuses